Peran Motivasi Belajar Dalam Memediasi Lingkungan Keluarga Dan Kemandirian Belajar Terhadap Hasil Belajar Akuntansi Keuangan Menengah 1 - Lestari, Dwi Rahma; Listiadi, Agung (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This research aims to analyze the effect of learning motivation as a mediation variable between family environment and independent learning on intermediate Financial Accounting I learning Outcomes. This study uses quantitative approach. The sampling techniques using purposive sampling so that 112 students were obtained as respondents. Data collection techniques through questionnaires and documentation. Data were analyzed using classical assumption test, regression analysis, path analysis and sobel test . The findings in this study show that (1) family environment have significant direct impact on intermediate Financial Accounting learning Outcomes. (2) Independent learning have significant direct impact on intermediate Financial Accounting learning Outcomes. (3) learning motivation have significant direct impact on intermediate Financial Accounting learning Outcomes. (4) family environment have significant direct impact on learning motivation. (5) Independent learning have significant direct impact on learning motivation. (6) Learning motivation cannot mediate family environment on intermediate Financial Accounting learning Outcomes. (7) Learning motivation mediate independent learning on intermediate Financial Accounting learning Outcomes.